Elastodynamic analysis of anisotropic elastic solid with multiple nanocavities. Issue 1 (3rd March 2016) - Parvanova, Sonia; Vasilev, Georgi; Dineva, Petia
Abstract: 2D elastodynamic problem for a finite elastic anisotropic solid with nanosized cavities is worked out in this paper. The solid under plane strain conditions is subjected to time-harmonic load. The developed computational tool for the steady-state problem is boundary integral equation method based on frequency-dependent fundamental solutions for elastic anisotropic continuum obtained by Radon transform. Accuracy of the dynamic stress concentration factor and displacement components is proven by comparisons with existing in the literature analytical solution and with the results obtained using commercial finite element package. In addition, a parametric study is performed in order to examine the sensitivity of the dynamic stress concentration field to the geometrical configuration of multiple cavities, to the characteristics of the surface elastic properties, to the type of orthotropy and to the dynamic interaction between cavities.